The legal stance of the Russian Constitutional Court on issues of propaganda and public demonstration of symbols and attributes - K. O. Rusinova (Proceedings of Southwest State University. Series: History and Law, 2026)
Relevance. The legislative ban on propaganda and public display of symbols and paraphernalia subject to a legal ban is an important tool in ensuring the national security of the state. At the same time, law enforcement practice raises discussions about the proportionality of restrictions on constitutional rights and freedoms. The purpose of the study is to analyze the legal positions of the Constitutional Court of the Russian Federation on the issues of propaganda and public demonstration of symbols and paraphernalia subject to a legal ban. The objectives are to identify the legal grounds and boundaries: of the ban; to determine the protected legal goods and their significance for the characteristics of the object of criminal law protection; to analyze the approach of the Constitutional Court of the Russian Federation on the balance between public and private interests; to assess the Court's position on the operation of the law over time. Methodology. The research is based on general scientific and private scientific research methods: formal legal, comparative legal methods, legal modeling method, specific sociological method, as well as logical research methods. Results. Based on the analysis of the definitions of the Constitutional Court of the Russian Federation, it was possible to establish that the mechanisms of negative (retrospective) liability: administrative and tort (Article 20.3 of the Administrative Code of the Russian Federation) and criminal law (Article 2824 of the Criminal Code of the Russian Federation, taking into account the sign of repetition), providing for responsibility for propaganda and public demonstration of symbols and attributes are used by the state as part of the implementation of obligations assumed to ensure the foundations of the constitutional order, respect for human and civil rights and freedoms. The key point is that the Court has shifted the legal emphasis from the formal demonstration (propaganda) of symbols and paraphernalia to countering the destructive ideology they represent. A system of legal guarantees has been identified that determine the proportionality of restrictions and respect for public and private interests. Conclusons. The legal positions of the Constitutional Court of the Russian Federation form the constitutional and legal guidelines for uniform law enforcement in this area.